2022
DOI: 10.1002/acr.24856
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors, and Mortality of Clinical and Subclinical Rheumatoid Arthritis–Associated Interstitial Lung Disease: A Population‐Based Cohort

Abstract: To identify the incidence, risk factors, and outcomes of rheumatoid arthritis-associated interstitial lung disease (RA-ILD) and to assess time trends in the incidence and mortality in RA-ILD.Methods. We included adult residents of Olmsted County, Minnesota with incident RA between 1999 and 2014. Subjects were followed until death, emigration, or April 30, 2019. ILD was defined as the presence of a radiologistdefined pattern consistent with ILD on chest computed tomography (CT). When chest CT was absent, the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…In a recent study of over 645 American patients diagnosed with RA, Samhouri et al observed a comparable frequency of RA-ILD and reported it to be 67.0% [21]. Our observation is also in line with an Egyptian study where Samy et al evaluated lung function among 160 RA patients and reported RA-ILD in 63.8% of patients.…”
Section: Discussionsupporting
confidence: 91%
“…In a recent study of over 645 American patients diagnosed with RA, Samhouri et al observed a comparable frequency of RA-ILD and reported it to be 67.0% [21]. Our observation is also in line with an Egyptian study where Samy et al evaluated lung function among 160 RA patients and reported RA-ILD in 63.8% of patients.…”
Section: Discussionsupporting
confidence: 91%
“…An assessment of patients with ILD who did not fulfil the classification criteria for RA revealed a third of patients who were ACPA-positive developed RA less than three years of their ILD diagnosis (36). Furthermore, there is a significant proportion of patients with RA (27% to 48%) for whom the diagnosis of ILD precedes or occurs at the same time as the onset of RA (5, 37, 38). Of note, a majority of individuals who developed ILD prior to RA were found to have a radiological UIP pattern (37).…”
Section: Discussionmentioning
confidence: 99%
“…In previous RA cohort follow-up studies, the types of comorbidities that can affect RA activity was focused upon ( 63 , 64 ). Although they have investigated the influence of circulatory system diseases and lipoprotein metabolic disorder on RA activity ( 65 ), none have explored the influence of TCM on the readmission of patients with RA-HL.…”
Section: Discussionmentioning
confidence: 99%